The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/molecules26092621
|View full text |Cite
|
Sign up to set email alerts
|

Drying Effects on Chemical Composition and Antioxidant Activity of Lippia thymoides Essential Oil, a Natural Source of Thymol

Abstract: Leaves of Lippia thymoides (Verbenaceae) were dried in an oven at 40, 50 and 60 °C and the kinetic of drying and the influence of the drying process on the chemical composition, yield, and DPPH radical scavenging activity of the obtained essential oils were evaluated. The composition of the essential oils was determined with gas chromatography-mass spectrometry and gas chromatography-flame ionization detection analyses. The influence of drying on the chemical composition of the essential oils of L. thymoides w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…The chemical compositions of the EOs of C. goetheanus (A, B, and C), were analyzed using a Shimadzu QP-2010 plus (Kyoto, Japan) a gas chromatography system equipped with an Rtx-5MS capillary column (30 m × 0.25 mm; 0.25 µm film thickness) (Restek Corporation, Bellefonte, PA, USA) coupled to a mass spectrometer (GC/MS) (Shimadzu, Kyoto, Japan). The program temperature was maintained at 60–240 °C at a rate of 3 °C/min, with an injector temperature of 250 °C, helium as the carrier gas (linear velocity of 32 cm/s, measured at 100 °C), and a splitless injection (1 μL of a 2:1000 hexane solution), using the same operating conditions as described in the literature [ 6 , 88 , 89 , 90 ]). The components were quantified using gas chromatography (GC) on a Shimadzu QP-2010 system (Kyoto, Japan), equipped with a flame ionization detector (FID) (Kyoto, Japan), under the same operating conditions as before, except for the carrier hydrogen gas.…”
Section: Methodsmentioning
confidence: 99%
“…The chemical compositions of the EOs of C. goetheanus (A, B, and C), were analyzed using a Shimadzu QP-2010 plus (Kyoto, Japan) a gas chromatography system equipped with an Rtx-5MS capillary column (30 m × 0.25 mm; 0.25 µm film thickness) (Restek Corporation, Bellefonte, PA, USA) coupled to a mass spectrometer (GC/MS) (Shimadzu, Kyoto, Japan). The program temperature was maintained at 60–240 °C at a rate of 3 °C/min, with an injector temperature of 250 °C, helium as the carrier gas (linear velocity of 32 cm/s, measured at 100 °C), and a splitless injection (1 μL of a 2:1000 hexane solution), using the same operating conditions as described in the literature [ 6 , 88 , 89 , 90 ]). The components were quantified using gas chromatography (GC) on a Shimadzu QP-2010 system (Kyoto, Japan), equipped with a flame ionization detector (FID) (Kyoto, Japan), under the same operating conditions as before, except for the carrier hydrogen gas.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have shown that the inhibition potential of essential oils for the free radicals DPPH and ABTS is higher than that of the Trolox standard, as in the case of the essential oils of Eugenia patrisii , E. punicifolia , and Myrcia tomentosa [ 31 ]. Some studies have also reported that a high thymol content may favor higher potential inhibition for essential oils, in which thymol is a major constituent [ 42 ]. This is a result of the presence of hydroxyl radicals that facilitate the capture of free radicals and reduce the effects of lipid oxidation [ 70 ].…”
Section: Antioxidant Activity Of Essential Oilsmentioning
confidence: 99%
“…Additionally, the content of the active ingredients of fresh herbs is much higher than their dried forms, which undergo a series of physical and chemical processes. The drying process may lead to the degradation of some of the chemical components of fresh herbs, especially heat-sensitive compounds, such as polyphenols, phenolic acids, and volatile oils [ 3 , 4 , 5 ], etc. Compared with dried Portulaca oleracea L. (POL) extracts, the fresh extract showed stronger antidiabetic activity and the relative contents of polyphenols and alkaloids were more abundant [ 6 ].…”
Section: Introductionmentioning
confidence: 99%